THE EFFORTS TO IMPROVE READING SKILL ON SHORT FUNCTIONAL TEXT APPLIED WORD STRESS LEARNING - Zulpan; Imam Tobroni; Akhir Hastinah (Jurnal Literasiologi, 2018)
The objective of this study is to improve the students' words stressing on reading short functional text. This research method is classroom action research using two cycles, it have three stages are planning, orientation, implementation. The first cycle, discussion and reflection at the end of the later action until planning the correction phase in the second cycle. The research subjects were in the class of 33 students of class VIII-D of SMP Negeri 2 Purwokerto. Data collection in this study is observation, which is an observation sheet to see how far the action has been achieved in the students' words stressing when reading short functional text. The results of the research in the first cycle were 3 students in the poor category, 18 students in the medium category and 12 students in the good category in words stressing on reading short functional text. The results of the second cycle of 22 students well-skilled and 11 students medium-skilled in reading on words stressing, and there were no more students who were less-skilled at reading short functional text on word stress. It can be concluded that there is an increase in word stress skills when reading short functional text from the first cycle to the second cycle in action.